The effect of pulmonary functions and respiratory muscle strength on sports performance in elite archers - Selçuk, Z.; Saka, S.; Ertan, H. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: The physical, physiological, and functional characteristics of archers affect target shooting performance. In our observational study, we aimed to examine the effect of pulmonary functions and respiratory muscle strength on sports performance in archers.